Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/14767058.2017.1325865
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Aloe vera gel and sweet almond oil on striae gravidarum in nulliparous women

Abstract: Aloe vera and sweet almond oil creams reduce the itching of striae and prevent their progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…In a nonrandomized study, Tashan and Kafkasli (2012) have demonstrated that massage with bitter almond oil may be effective in reducing the visibility of current striae gravidarum, and in the prevention of new striae [ 105 ]. Other formulations have been shown to ameliorate striae itching [ 106 ]. However, other products containing almond oil have not shown to have similar benefit [ 140 ].…”
Section: The Potential Beneficial Effects Of Topical Application Omentioning
confidence: 99%
See 1 more Smart Citation
“…In a nonrandomized study, Tashan and Kafkasli (2012) have demonstrated that massage with bitter almond oil may be effective in reducing the visibility of current striae gravidarum, and in the prevention of new striae [ 105 ]. Other formulations have been shown to ameliorate striae itching [ 106 ]. However, other products containing almond oil have not shown to have similar benefit [ 140 ].…”
Section: The Potential Beneficial Effects Of Topical Application Omentioning
confidence: 99%
“…However, other products containing almond oil have not shown to have similar benefit [ 140 ]. For example, sweet almond oil in creams are more effective than the base cream at ameliorating the itching of striae and preventing its progression [ 106 ]. In a study by Sultana et al done with murine models, topical almond oil was shown to prevent the structural damage caused by UV irradiation [ 107 ].…”
Section: The Potential Beneficial Effects Of Topical Application Omentioning
confidence: 99%
“…AV inhibits the adhesion of leukocytes and pro‐inflammatory cytokines such as tumour necrosis factor‐alpha, interleukin–6 and interleukin–8 and increases anti‐inflammatory cytokines (Burusapat et al., 2018; Takzare et al., 2009; Tamura et al., 2009). In addition to the abovementioned characteristics, AV affects fibroblast growth factor receptors, stimulates proliferation, and enhances collagen production, as a regenerative product (El‐Gammal et al., 2018; Eshghi et al., 2010; Ghafarzadeh & Eatemadi, 2017; Hajhashemi et al., 2018). Due to these beneficial effects, AV accelerates wound contraction and increases the breaking strength of resulting scar tissue and synthesis of hyaluronic acid and dermatan sulphate in the granulation tissue of a healing wound (Foster et al., 2011; Radha & Laxmipriya, 2015; Tanaka et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of SG striae is still unclear. Genetic factors, hormonal factors, and increased mechanical stress in the connective tissue have been implicated in the etiopathogenesis of SG 3,4 . Many studies investigated possible etiologic factors related to the presence of SG.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors, hormonal factors, and increased mechanical stress in the connective tissue have been implicated in the etiopathogenesis of SG. 3,4 Many studies investigated possible etiologic factors related to the presence of SG. Lurie et al found lower serum levels of relaxin at 36 weeks of gestation in women with SG compared with women without this finding.…”
Section: Introductionmentioning
confidence: 99%